Integrating Digital Microlearning into Pragmatic Instruction: TikTok-Assisted Simulation in Negotiation Speaking Education - Sofia Yanifah; Isah Cahyani; Novi Resmini; Encep Kusumah; Teti Sobari (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2026)
The background of this research stems from students’ inadequate speaking abilities caused by passive attitudes, lack of confidence, and limited practice opportunities. This study aims to measure the effectiveness of the TikTok-Assisted Simulation Learning Model in improving negotiation speaking skills among high school students. A quantitative quasi-experimental approach with a nonequivalent control group design was applied, involving 36 students in the experimental class and 36 in the control class. Data were collected through pre-test and post-test instruments. Since the data did not follow a normal distribution, the Mann-Whitney U test was employed as the analytical tool, yielding an Asymp. Sig. (2-tailed) value of 0.000 (P < 0,05), which indicates a statistically significant difference between the two groups. Furthermore, N-Gain analysis revealed a mean score of 0.59 (moderate category) in the experimental group and 0.28 (low category) in the control group. These findings demonstrate that the TikTok-Assisted Simulation Learning Model is an effective, innovative, and applicable learning alternative for negotiation speaking at the high school level.